Postural control in subjects with visual impairment - Schwesig, René; Goldich, Yakov; Hahn, Ales; Müller, Anja; Kohen-Raz, Reuven; Kluttig, Alexander; Morad, Yair (European journal of ophthalmology, 2011)
To investigate the effect of long-term, not experimentally induced visual impairment on balance, and to clarify which means are used to compensate for this sensory deficit. Posturography was examined in 50 visually impaired subjects (11 with congenital blindness and 39 with acquired visual impairment) and 50 healthy controls. Examination was performed in 4 testing conditions: while standing on firm surface or foam pads (which decreases the somatosensory input) and with open or closed eyes (manipulating visual input). Subjects with acquired visual impairment were significantly less stable than controls when tested with open eyes, especially when standing on foam pads, but equal to controls when eyes were closed. Congenitally blind subjects performed equally to normal controls in all test conditions when tested with eyes open, and performed significantly better than controls with eyes closed. In comparison to subjects with acquired visual impairment, the congenitally blind were significantly more stable in all test conditions. Fourier analysis revealed that the visually impaired subjects showed decreased intensity values within the lowest frequency range of 0.1 Hz and below, a range believed to be sensitive to the function of the visual system. We have found that vision impairment influenced postural control, especially if acquired and not congenital. The somatosensory and vestibular systems serve as compensatory mechanisms, which is utilized most effectively by the congenitally blind.